“Elaboración de una bebida carbonatada a partir de pulpa de naranjilla (Solanum Quitoense) con adición de leche de semillas de cáñamo (Cannabis Sativa SSP. Sativa)”. - Yanchatipán Lema, Alexander Paúl (2023)
The project had as aim to elaborate a carbonated drink based naranjilla (Solanum quitoense) pulp with the hemp seed milk addition (Cannabis sativa ssp. sativa), applying a completely randomized block design in A*B factorial arrangement (3*3), where factor A was the relation (naranjilla pulp and hemp seed milk) and factor B, they were the drink carbonation levels, through incorporating CO2. For the drink, it was made 9 treatments with 3 repetitions, respectively. They were used as preservative (potassium sorbate) and citric acid, according established, then, homogenization, the drink was subjected to a pasteurization process at a 75 °C temperature for 15 minutes for its subsequent packaging, into high-density polyethylene 500 ml containers. It was made the physical-chemical analysis all the treatments, by getting T7 as the best treatment, which corresponds to the naranjilla pulp and hemp seed milk (70%-30%) carbonated at 2 CO2 volumes relation. Further, it was made the effervescence, color, appearance, flavor, aroma, and acceptability sensory analysis with the eighth-semester students help from Agroindustry’s career, through the got results, it was determined as the best treatment to the T7. The drink was subjected to a physical-chemical analysis, where it was got a 1,9 CO2/L, 8,47 °Brix, pH 2,80, acidity 5% carbonation level into citric acid. Further, it was made a nutritional analysis, resulting in, a 0,32% protein content, fat 0,31%, cholesterol <0,01 mg/100g, sodium 8,44 mg/100g, carbohydrates 8,40%, calories 37,67 Kcal /100g, fiber 0,00%, total sugars 7,21% and ash 0,24%. It was also made a microbiological analysis, by finding, which it complies with the NTE INEN 1101 standard provisions for carbonated beverages. The drink retail price is $1,34 of a 500 ml presentation that is an acceptable price for the consumer.